2021
DOI: 10.4012/dmj.2020-207
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a new polishing system on changes in gloss and surface roughness of resin composites after polishing and brushing

Abstract: This study aimed to compare the change of surface roughness (Ra) and gloss units (GU) of five dental composites (Filtek Z250, Filtek Z350XT, Metafil CX, Ceram X one, and Venus Diamond) polished with three systems (Sof-Lex XT, Enhance/Pogo, and Sof-Lex Diamond) before/after simulated brushings and to determine the amount of time required to achieve maximum gloss. Ninety rectangular specimens (n=18 per composite) were prepared. Six specimens of each composite were assigned to one of the polishing systems. The Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 37 publications
(43 reference statements)
3
37
0
2
Order By: Relevance
“…Twenty‐nine articles were included to address the second aim of the study that focused on the effect of toothbrush abrasion on the maintenance of high gloss/smoothness of different composite formulations and these are summarized in Table 3 53–81 . A more detailed table containing all the specific Ra/Sa and GU data for each material/polisher combination, for before and after toothbrush abrasion, is presented in Supplemental Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐nine articles were included to address the second aim of the study that focused on the effect of toothbrush abrasion on the maintenance of high gloss/smoothness of different composite formulations and these are summarized in Table 3 53–81 . A more detailed table containing all the specific Ra/Sa and GU data for each material/polisher combination, for before and after toothbrush abrasion, is presented in Supplemental Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…In general, resin composites with finely‐sized fillers are more wear resistant compared to those with larger fillers 86–90 . In this literature review, only five studies out of 24 showed composites with larger particle sizes to have a greater increase in roughness after toothbrushing 58,74,75,77,81 . Valente 2013 81 and Salgado 2013 75 used a series of experimental resin composites with systematically varied filler sizes to assess the effect of filler size on Ra.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, resilience was calculated using the data provided from flexural testing. The collected data showed that ceram.X Universal presented the lowest modulus of resilience among the groups for all evaluated time points which could be attributed to the type of filler and monomer present on the material [35][36][37] . Furthermore, compared to the other groups Dyract eXtra presented a lower resilience modulus notably in the first 24 h. TPH Spectra HT LV and Spectrum TPH3 showed consistent modulus of resilience after 1 h, 24 h, 1 week and 1 month.…”
Section: Discussionmentioning
confidence: 93%
“…In addition to non-agglomerated barium glass, ceram.X Universal also contains pre-polymerized fillers, which Kim et al 25) suggest may be more susceptible for lower flexural strength. Sang et al 35) discussed that the filler content of ceram.X Universal may be more susceptible to particle loss and wear while Turssi et al 36) noted with ceram.X Universal that some of its nanosized filler particles might not provide preferential load support and be more susceptible to wear and surface volume loss. Furthermore, Bagheri et al 37) noted ceram.X Universal's subsurface degradation due to water absorption.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation